The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00412-014-0464-y
|View full text |Cite
|
Sign up to set email alerts
|

Transposons, environmental changes, and heritable induced phenotypic variability

Abstract: The mechanisms of biological evolution have always been, and still are, the subject of intense debate and modeling. One of the main problems is how the genetic variability is produced and maintained in order to make the organisms adaptable to environmental changes and therefore capable of evolving. In recent years, it has been reported that, in flies and plants, mutations in Hsp90 gene are capable to induce, with a low frequency, many different developmental abnormalities depending on the genetic backgrounds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 75 publications
3
66
2
Order By: Relevance
“…Barbara McClintock [1984] formerly suggested that the activity of mobile elements in the genome represented a reaction to environmental stressors. This hypothesis was supported by several other authors [Capy et al, 2000;Kidwell, 2002;Chénais et al, 2012;Piacentini et al, 2014], and numerous cases of transposon activation due to environmental stress conditions have been observed in plants, where one of the most influential environmental factors is represented by temperature [Vitte and Panaud, 2005;Kelly and Leitch, 2011;Chénais et al, 2012;Ito, 2013;Wheeler, 2013;Ishiguru et al, 2014;Kim et al, 2014]. Examples of correlations between environmental stressors and transposon activity are rarer in the animal kingdom.…”
Section: Mechanisms and Causessupporting
confidence: 62%
See 2 more Smart Citations
“…Barbara McClintock [1984] formerly suggested that the activity of mobile elements in the genome represented a reaction to environmental stressors. This hypothesis was supported by several other authors [Capy et al, 2000;Kidwell, 2002;Chénais et al, 2012;Piacentini et al, 2014], and numerous cases of transposon activation due to environmental stress conditions have been observed in plants, where one of the most influential environmental factors is represented by temperature [Vitte and Panaud, 2005;Kelly and Leitch, 2011;Chénais et al, 2012;Ito, 2013;Wheeler, 2013;Ishiguru et al, 2014;Kim et al, 2014]. Examples of correlations between environmental stressors and transposon activity are rarer in the animal kingdom.…”
Section: Mechanisms and Causessupporting
confidence: 62%
“…Examples of correlations between environmental stressors and transposon activity are rarer in the animal kingdom. However, similar connections were noted in Drosophila melanogaster , where differences in the rate of transposition were related to the development of temperature [Capy et al, 2000;Kim et al, 2014;Piacentini et al, 2014] and to the development of a resistance to pesticides [Chénais et al, 2012]. In human cells a reorganization of the transcriptome after thermal shock was described, putatively involving SINE transposon sequences [Wheeler, 2013].…”
Section: Mechanisms and Causesmentioning
confidence: 86%
See 1 more Smart Citation
“…Instead, careful (and laborious) work, such as that done by some (Brink 1956;Clark and Carbon 1985;Steiner and Clarke 1994;De Vanssay et al 2012) showing frequent switching, should be considered strong evidence in the place of exhaustive sequencing. We must, however, always be concerned with the possibility of efficient inducible changes masquerading as "epigenetic" cases, e.g., mating type switching in yeasts (Haber 1998), VDJ recombination (Blackwell and Alt 1989), repeat-sequence instability (Hawley and Marcus 1989), and induced mutation (McClintock 1983;Piacentini et al 2014); after all, they do bear all of the hallmarks of epigenetic changes save one: we happen to know their mechanism. For that reason, it is critical to refrain from negative claims (that is, assertions of "no difference") as implied in "genetically identical chromosomes," when chromosomes have not been sequenced.…”
Section: The Test(s)mentioning
confidence: 99%
“…Some of them may lead to genetically determined phenotypic variability. One of the mech− anisms responsible for the formation of genetic variability is associated with the presence of transposable elements (TE) (Kalendar et al 2000;Piacentini et al 2014). These mobile genetic elements have a significant impact on the organiza− tion, plasticity and evolution of genomes (Frost et al 2005).…”
Section: Introductionmentioning
confidence: 99%